Pengaruh Pengungkapan Emisi Karbon, Tata Kelola Perusahaan dan Kinerja Keuangan: Studi Di Indonesia - Mukhzarudfa Mukhzarudfa; Wiwik Tiswiyanti; Diana Safutri (Universitas Muhammadiyah Malang, 2023)
Purpose: This study was conducted to investigate how disclosure of carbon emissions, management structure, and ownership structure impact the financial performance of businesses, as measured by profitability ratios such as return on assets (ROA), return on equity (ROE), and net profit margin (NPM). Methodology/approach: The research data is sourced from the Annual Report and Sustainability Report of Energy Companies Listed on the IDX (Indonesian Stock Exchange) 2019-2021. This study uses PLS-SEM analysis and Smart-PLS software. Findings: The results show that disclosure of carbon emissions has no impact on company financial performance, management structure has a significant positive impact on financial performance, and ownership structure is found to have no impact on financial performance. Practical and Theoretical contribution/Originality: The implications of this research are expected to help management understand the factors that can maximize financial performance. In addition, potential investors are expected to be able to use the findings of this study to help them assess the condition of the company before making investment decisions. Novelty of this research in this new study, three independent variables were used: disclosure of carbon emissions, management structure, and ownership structure. In addition, there is one dependent variable, namely financial performance.